SIMULASI NUMERIK FINITE ELEMENT METHOD (FEM) UNTUK OPTIMALISASI PENAMPANG U-DITCH 2 m TERHADAP PELAKSANAAN HANDLING - Malik Mushthofa (TEKNISIA, 2019)
Increasing of precast concrete usage in many sectors automatically spur fabricators to improve their products quality. Related to that, the application of u-ditch type 2 m domestic product, during product handling (when concrete was 7 hours old) many cracks occurs at the section. Therefore, this optimization aim to improve the product quality. In addition, this optimization also supports to increase production capacity due to the reinforcement volume. The results obtained from FEM simulation, stress distribution is more favorable in the modified cross section. Stress distribution of the section inner corner (cracks zone of existing section), turn from tension become compression and then turn again to tension. Meanwhile, modified section give different stress distribution, stress transition from compression turn back again to tension not happen here. While the evaluation due to the strain value, the modified cross section gives a smaller strain value than the existing cross section strain. In addition, this optimization results in a decrease in reinforcement volume by 10.54%.